Neoadjuvant Chemotherapy, Excision, and Observation for Early Rectal Cancer: The Phase II NEO Trial (CCTG CO.28) Primary End Point Results. Issue 2 (18th August 2022) - Kennecke, Hagen F.; O'Callaghan, Chris J.; Loree, Jonathan M.; Moloo, Hussein; Auer, Rebecca; Jonker, Derek J.; Raval, Manoj; Musselman, Reilly; Ma, Grace; Caycedo-Marulanda, Antonio; Simianu, Vlad V.; Patel, Sunil; et al.
Abstract : PURPOSE: Organ-sparing therapy for early-stage I/IIA rectal cancer is intended to avoid functional disturbances or a permanent ostomy associated with total mesorectal excision (TME). The objective of this phase II trial was to determine the outcomes and organ-sparing rate of patients with early-stage rectal cancer treated with neoadjuvant chemotherapy followed by transanal excision surgery (TES). METHODS: This phase II trial included patients with clinical T1-T3abN0 low- or mid-rectal adenocarcinoma eligible for endoscopic resection who were treated with 3 months of chemotherapy (modified folinic acid–fluorouracil-oxaliplatin 6 or capecitabine-oxaliplatin). Those with evidence of response proceeded to transanal endoscopic surgery 2-6 weeks later. The primary end point was protocol-specified organ preservation rate, defined as the proportion of patients with tumor downstaging to ypT0/T1N0/X and who avoided radical surgery. RESULTS: Of 58 patients enrolled, all commenced chemotherapy and 56 proceeded to surgery. A total of 33/58 patients had tumor downstaging to ypT0/1N0/X on the surgery specimen, resulting in an intention-to-treat protocol-specified organ preservation rate of 57% (90% CI, 45 to 68). Of 23 remaining patients recommended for TME surgery on the basis of protocol requirements, 13 declined and elected to proceed directly to observation resulting in 79% (90% CI, 69 to 88) achieving organ preservation. The remaining 10/23 patients proceeded to recommended TME of whom seven had no histopathologic residual disease. The 1-year and 2-year locoregional relapse-free survival was, respectively, 98% (95% CI, 86 to 100) and 90% (95% CI, 58 to 98), and there were no distant recurrences or deaths. Minimal change in quality of life and rectal function scores was observed. CONCLUSION: Three months of induction chemotherapy may successfully downstage a significant proportion of patients with early-stage rectal cancer, allowing well-tolerated organ-preserving surgery.